Enhancing Higher Education Quality Through Internal Audit Practices - Farras Luthfi, Nabillah; Murdhaningsih; Anisah Harared, Bunga (Journal of Economics, Business, and Government Challenges, 2024)
To maintain and improve quality and academic services, universities need an internal audit system that covers governance and educational aspects. Internal audit is responsible for monitoring and evaluating the implementation of higher education institutions' work plans. This study examines the role of internal audit in higher education through a literature review of previous studies. The results show that internal audit is important in building and improving the quality of higher education. By ensuring the effectiveness of the organisation's risk management framework, internal audit can help higher education institutions face governance challenges. Additionally, internal audits support the implementation of the three lines of the defence model, which integrates multiple layers of defence within an organisation to achieve strategic objectives. The role of an internal audit includes not only the oversight of regulatory compliance but also the strengthening of senior management's decision-making processes. Overall, internal audits are a control tool and a strategic partner in improving higher education quality. This conclusion underscores the critical role of a robust internal audit function in ensuring the success of higher education institutions in delivering high-quality academic services.